COMPARISON OF THE POLITICAL DYNASTY IN BANTEN PROVINCE WITH THE POLITICAL DYNASTY IN CENTRAL MALUKU DISTRICT - Sufajar, Rahmat; Guridno, Aberar (Journal of Social Political Sciences, 2021)
The article of this study tries to explain political dynasties by making a comparison between political dynasties in Banten province and political dynasties in Central Maluku district. The political dynasties in these two regions have similarities in the basic framework of kinship relations, but the political dynasties in Central Maluku also show the dominance of the Hatuhaha Group in a strategic position in the social life of the people in Central Maluku and Maluku. This study also produces findings that local officials who carry out political dynasties focus on the economic and political interests of their groups and cause corruption in the management of power. In collecting data using library research method. The result showed that Political dynasties also show the weakness of political parties in the recruitment of regional leaders so that democracy at the local level is trapped by the interests of groups from the political dynasty.